(untitled) - Konecny, Daniel; Konecny, Vladimir (Doprava a spoje, 2006)
The paper deals with carbon dioxide production of transport sector in Slovakia. Article includes new point of view on CO2 production in transport sector and proposes new calculation method for identification of amount of direct and indirect CO2 emissions caused by transport sector. It is realized in order to compare carbon dioxide emissions impacts onto greenhouse effect.